Mayhem at a Halloween wedding - Duncan, Emmeline (Duncan, Emmeline. Halloween bookshop mysteries, 2025)
"It's Halloween year-round in Elyan Hollow, Oregon, where Bailey Briggs sells the latest tomes of frights and fears at the bustling Lazy Bones Books-when she's not uncovering deadly secrets and mysteries that haunt the town . . . There's more to celebrate this Halloween when Bailey's college friend Raven prepares to walk down the aisle in spooky seasonal style. As a bridesmaid, Bailey is overwhelmed helping with wedding preparations while the annual holiday festival scares up business for her bookstore. She also finds herself playing peacekeeper between fellow bridesmaids Colby and Ivy, whose arguments add even more conflict to the already simmering tensions within the wedding party between the groom's traditional family and the bride's bohemian parents. Trying to ease stress and enjoy the spirit of the season, Bailey arranges the bachelorette party on the night of the Halloween parade. Everyone agrees to join in the festivities and dress up in costume. But running into several people dressed as the Grim Reaper turns out to be a bad omen. An explosion rocks the route, causing a panic. When the smoke clears, Ivy is found dead, believed to be murdered-and Colby is questioned by police after several witnesses report the very public clashes between the two bridesmaids. Narrowing down the list of suspects to prove Colby's innocence means Bailey will have to find a motive that drove a killer-and keep her friend's wedding bells from becoming funeral knells . . ."--